High energy flexible supercapacitors formed via bottom-up infilling of gel electrolytes into thick porous electrodes - Xiangming Li (Nature Portfolio, 2018)
The development of high performance flexible solid supercapacitors calls for an effective approach to infill gel electrolytes into porous electrodes. Here the authors report a bottom-up method to address this technical challenge, which leads to enhanced areal capacitance and durability.